**Answer:**

A

**Step-by-step explanation:**

**Answer:**

910

**Step-by-step explanation:**

<u />

**Answer:**

1

**Step-by-step explanation:**

Divide: 3 : 1

3

= 3

1

· 3

1

= 3 · 3

1 · 1

= 9

1

= 9

Dividing two fractions is the same as multiplying the first fraction by the reciprocal value of the second fraction. The first sub-step is to find the reciprocal (reverse the numerator and denominator, reciprocal of 1

3

is 3

1

) of the second fraction. Next, multiply the two numerators. Then, multiply the two denominators.

In words - three divided by one third = nine.

Subtract: 9 - the result of step No. 1 = 9 - 9 = 0

Add: the result of step No. 2 + 1 = 0 + 1 = 1